Trabajo y familia : entrelazamiento de trayectorias vitales - Blanco, Mercedes (El Colegio de México A.C., 2002)
This article examines the well-known link between work and family beginning with a relatively unexplored platform: the diachronic perspective that describes processes over time. This problem falls within the theoretical-methodological approach known as the course of life and basically uses one of the tools utilized in this perspective: the trajectory. The main objective is therefore to analyze the link between some of the main life trajectories (school, work, marriage and child- bearing) in shaping the course of life of a group of women from the middle class sectors in Mexico City. Within this process, particular attention is paid to the work trajectory in order to use it as an axis and analyze its interrelationship with the others and ascertain under what circumstances it acquires pre-eminence. Finally, by combining the links between the life trajectories considered, the author proposes a typology in order to describe the different forms acquired by the family-work dyad and thereby identify both the shared characteristics and the existing differences within an apparently highly similar universe, thereby rejecting the assumption of homogeneity based on class, gender and stage in the life cycle.